A high temperature resistant anti-corrosion coating and preparation method thereof
By combining epoxy resin and organic-inorganic hybrid resin, the cross-linking density and corrosion resistance of the coating are improved, and the problem of poor durability of existing anticorrosion coatings in high temperature environments is solved, and a long time of more than 250℃ is achieved Durability and multiple hot and cold cycle capabilities reduce maintenance frequency and production costs.
Patent Information
- Application Number
- CN202310888717.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-07-19
AI Technical Summary
The existing anticorrosion coatings have poor durability in high temperature environments and cannot meet the long-term anticorrosion requirements of above 250℃, resulting in aging of the coating and degradation of protective performance, increasing the maintenance frequency and production costs.
Epoxy resin and organic-inorganic hybrid resin are used as main components, combining glass flakes, precipitated barium sulfate, talc powder and phenoamine, and improving coating cross-linking through Si-O-Si bond condensation in organic-inorganic hybrid resin Density, improve temperature resistance, and form a stable coating through phenoamine curing reaction.
The coating has achieved high temperature resistance of 500 hours above 250℃, maintained good salt spray and humidity resistance, and can withstand more than 50 hot and cold cycles from 250℃ to 20℃, extending the service life of the coating.
Smart Images

Figure CN116875148B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an anti-corrosion coating, and in particular to a high temperature resistant anti-corrosion coating and a preparation method thereof. Background Art
[0002] Corrosion under insulation and corrosion prevention have always been a global problem. The losses caused by corrosion under insulation can reach billions of dollars each year. These losses include equipment damage, factory shutdowns, maintenance losses, and subsequent repairs and maintenance, etc., and may also cause personal injury and death accidents. In recent years, major petrochemical companies and coatings manufacturers have increased their investment in the research of corrosion under insulation mechanisms and anti-corrosion coatings in order to find solutions to corrosion prevention under insulation. Although epoxy coatings have excellent anti-corrosion properties, their maximum continuous temperature resistance limit is 150°C, which cannot meet the anti-corrosion requirements under insulation with higher temperature resistance limits; although traditional silicone coatings have excellent temperature resistance, their anti-corrosion performance is not as good as epoxy coatings, and they cannot be used as anti-corrosion materials under insulation. The maximum continuous temperature resistance limit of phenolic epoxy heat-resistant coating is 200℃, which can solve the disadvantage that traditional epoxy coating cannot be used for a long time in the range of 150~200℃; at the same time, the heat-resistant coating has excellent anti-corrosion performance and can meet the anti-corrosion requirements under the insulation layer in the range of 0~200℃. With the development of industry, higher requirements are put forward for the heat resistance of the coating, and the long-term temperature is as high as 250℃ or even higher. In order to improve the anti-corrosion performance and heat resistance of the anti-corrosion coating. At present, the products on the market shelf can withstand a temperature of 250℃ for a short time, but cannot meet the requirements of long-term 250℃ and the requirements of long-term 250℃ and alternating corrosive environment.
[0003] When epoxy anti-corrosion coating and phenolic epoxy anti-corrosion coating work for a long time in an environment above 200℃, the coating will age to a certain extent. When the temperature of the protected workpiece decreases, the protective performance of the coating on the workpiece will decrease, and the workpiece will be easily corroded by the environmental medium. Therefore, the anti-corrosion performance of epoxy anti-corrosion coating and phenolic epoxy anti-corrosion coating decreases after high temperature, resulting in an increase in maintenance frequency, reducing the effective working time of the workpiece, and directly or indirectly increasing the production cost. Therefore, it is necessary to develop a high temperature resistant anti-corrosion coating with a longer life. Summary of the invention
[0004] In view of the problem that the above-mentioned anti-corrosion coating has poor high temperature resistance, the present invention provides a high temperature resistant anti-corrosion coating and a preparation method thereof. The coating can withstand temperatures above 250°C for a long time and still has good salt spray resistance, moisture resistance and other properties after a certain period of high temperature.
[0005] In order to achieve the above-mentioned object, the present invention provides a high temperature resistant anti-corrosion coating, which comprises component A and component B in a mass ratio of (1.1-4):1, wherein:
[0006] By weight, component A includes:
[0007] Epoxy resin 15~40 parts
[0008] 8~30 parts of organic-inorganic hybrid resin
[0009] Glass flakes 8~20 pieces
[0010] 3~8 parts of precipitated barium sulfate
[0011] 2~8 parts of talcum powder
[0012] 1~5 parts of pigment
[0013] Additives 0.05~5 parts
[0014] Solvent 0~20 parts;
[0015] Component B is phenalkamine.
[0016] The present invention adopts epoxy resin and organic-inorganic hybrid resin as main film-forming substances, glass flakes, precipitated barium sulfate, talcum powder and the like as pigments and fillers, and a curing agent is phenolic amine. The addition of the organic-inorganic hybrid resin improves the temperature resistance, corrosion resistance, moisture resistance and other properties of the anti-corrosion coating, and especially after being baked at a high temperature of 250° C. for 500 hours, the coating also has good salt spray resistance.
[0017] Specifically, the epoxy resin is a bisphenol A epoxy resin with an epoxy equivalent of 154 to 450. Preferably, at least one of YPE-128, YPE-6101X90, YPE-6101X80, and YPE-011X75 is used.
[0018] Specifically, the organic-inorganic hybrid resin is prepared from raw materials including the following components:
[0019] Acidic silica sol 2~30 parts
[0020] 10~30 parts of tetraethyl orthosilicate
[0021] 30~40 parts of methylsiloxane monomer
[0022] 5~15 parts of silane coupling agent containing epoxy group
[0023] Water 0~20 parts
[0024] 3~15 parts of solvent.
[0025] The organic-inorganic hybrid resin is prepared from silica sol, tetraethyl orthosilicate, methyl silane monomer, silane coupling agent containing epoxy group, distilled water, inhibitor, solvent, etc. The mass content of silicon in the organic-inorganic hybrid resin (calculated as silicon dioxide) is ≥30%, and the resin contains silanol and epoxy groups (whose structure is as followsFigure 1 As shown in the figure, the epoxy group in the resin reacts with the curing agent to form a coating crosslink at room temperature, ensuring that the coating has good performance at room temperature. As the temperature rises, when the ambient temperature is higher than 60°C, the silanol group will gradually condense to form Si-O-Si bonds, which can further increase the crosslinking density of the coating, increase the glass transition temperature of the coating, and thus improve the temperature resistance of the coating. The silanol equivalent is 500g / Eq~1500g / Eq, and the epoxy equivalent is 900g / Eq~3300g / Eq.
[0026] Preferably, the diameter of the acidic silica sol particles is 5-20 nm; and / or
[0027] The methylsiloxane monomer is at least one of methyltriethoxysilane and methyltrimethoxysilane; and / or
[0028] The epoxy group-containing silane coupling agent is at least one of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltriethoxysilane, γ-(2,3-epoxypropyloxy)propylmethyldimethoxysilane and γ-(2,3-epoxypropyloxy)propylmethyldiethoxysilane.
[0029] Preferably, the pigment is selected from at least one of titanium dioxide, carbon black, iron oxide red and phthalocyanine blue.
[0030] Preferably, the auxiliary agent is selected from at least one of polyamide wax, fumed silica, organic bentonite, BYK-A530, BYK-A525, BYK-A535 and BYK-333.
[0031] Preferably, the phenalkamine is selected from at least one of KMH-100, KMH-151, KMH-153, NX-2015, and NX-2018.
[0032] The second aspect of the present invention provides a method for preparing the above-mentioned high temperature resistant and anti-corrosion coating, wherein the preparation method of component A is: epoxy resin and organic-inorganic hybrid resin are evenly mixed, and then precipitated barium sulfate, talcum powder, pigment, and additives are added, and after mixing until the fineness is less than 50 μm, glass flakes and solvent are added and dispersed evenly.
[0033] Furthermore, the preparation method of the organic-inorganic hybrid resin is as follows: adding acidic silica sol to water, heating the system to a temperature of above 60°C, and then starting to drip a mixture of ethyl orthosilicate and methylsiloxane monomers, and completing the dripping in 2 to 3 hours. During the dripping process, the temperature of the reaction system is controlled to be between 60 and 65°C, and after the dripping is completed, the system temperature is cooled to less than 50°C, and then the solvent is added, and the temperature is raised to reflux of the system, and 20 to 40% of the solvent by weight of the system is evaporated and then cooled. After the temperature is less than 60°C, a silane coupling agent containing an epoxy group is added, and the temperature of the system is maintained between 60 and 65°C. After reacting for 1 to 1.5 hours, the system is cooled to room temperature.
[0034] Through the above technical solution, the present invention achieves the following beneficial effects:
[0035] The high temperature resistant and anti-corrosion epoxy coating prepared by the present invention has the following properties after curing: high temperature resistance of 250°C for not less than 500h, salt spray resistance for not less than 1000h, and resistance to cold and hot cycles from 250°C to 20°C for not less than 50 times. After baking at 250°C for 240h, the salt spray resistance is not less than 500h. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of the structure of an organic-inorganic hybrid resin in an embodiment of the present invention. DETAILED DESCRIPTION
[0037] The specific implementation of the present invention is described in detail below in conjunction with the examples. It should be understood that the specific implementation described herein is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0038] Example 1
[0039] 20g of acidic silica sol was added to the reactor, and the temperature was raised to 60°C, and then a mixture of 100g of ethyl orthosilicate and 300g of methyltriethoxysilane was added dropwise. The addition was completed in 2h. During the addition, the temperature of the reaction system was controlled between 60°C and 65°C. After the addition was completed, the system temperature was cooled to less than 50°C, and then 30g of solvent butanol was added. The temperature was raised to reflux, and 6g of solvent was evaporated and then cooled. After the temperature was less than 60°C, 50g of γ-(2,3-epoxypropoxy)propyltriethoxysilane was added, and the temperature of the system was maintained between 60°C and 65°C. After 1 hour, the system was cooled to room temperature to obtain YW-1 organic-inorganic hybrid resin. The mass content of silicon in the organic-inorganic hybrid resin was 31.6%, of which the silanol equivalent was 600g / Eq and the epoxy equivalent was 2700g / Eq.
[0040] At 300 rpm, add 150g epoxy resin and 80g YW-1 organic-inorganic hybrid resin into the reactor and stir for 40min until the system is uniform. Then add 30g precipitated barium sulfate, 20g talcum powder, 10g titanium dioxide and 0.5g polyamide wax at 300 rpm. Keep at 800 rpm for 4h, test the fineness of the coating to be less than 45μm, then reduce the speed, add 80g glass flakes at 300 rpm and disperse for 1.5h. Filter and package to obtain coating A component A-1.
[0041] Example 2
[0042] A mixture of 300g of acidic silica sol and 200g of distilled water was added to the reactor. When the temperature of the system reached 60°C, a mixture of 300g of ethyl orthosilicate and 400g of methyltriethoxysilane was added dropwise. The addition was completed in 3 hours. During the addition, the temperature of the reaction system was controlled between 60°C and 65°C. After the addition was completed, the system temperature was cooled to less than 50°C, and 150g of solvent xylene was added. The temperature was raised to reflux, 60g of solvent was evaporated, and the temperature was cooled. When the temperature was less than 60°C, 150g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added, and the temperature of the system was maintained between 60°C and 65°C. After 1.5 hours, the system was cooled to room temperature to obtain YW-2 organic-inorganic hybrid resin. The mass content of silicon in the organic-inorganic hybrid resin was 43.5%, of which the silanol equivalent was 1400g / Eq and the epoxy equivalent was 1000g / Eq.
[0043] At 500 rpm, add 400g epoxy resin and 300g YW-2 organic-inorganic hybrid resin into the reactor and stir for 50min until the system is uniform. Then add 80g precipitated barium sulfate, 80g talcum powder, 50g titanium dioxide and 50g polyamide wax at 500 rpm. Keep at 1000 rpm for 6h, test the fineness of the coating to be less than 50μm, then reduce the speed, add 200g glass flakes, 100g xylene and 100g butanol at 500 rpm and disperse for 3h. Filter and package to obtain coating A component A-2.
[0044] Example 3
[0045] A mixture of 220 g of acidic silica sol and 50 g of distilled water was added to the reactor. When the temperature of the system reached 60°C, a mixture of 180 g of ethyl orthosilicate and 390 g of methyltrimethoxysilane was added dropwise. The addition was completed in 2 hours. During the addition, the temperature of the reaction system was controlled to be between 60°C and 65°C. After the addition was completed, the system temperature was cooled to less than 50°C, and 60 g of butanol was added. The temperature was raised to reflux, 18 g of the solvent was evaporated, and the temperature was cooled. When the temperature was less than 60°C, 80 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 20 g of γ-(2,3-epoxypropoxy)propyltriethoxysilane were added. The temperature of the system was maintained between 60°C and 65°C. After 1 hour, the system was cooled to room temperature to obtain YW-3 organic-inorganic hybrid resin. The mass content of silicon in the organic-inorganic hybrid resin is 41.5%, wherein the silanol equivalent is 550 g / Eq, and the epoxy equivalent is 1700 g / Eq.
[0046] At 400 rpm, add 200g epoxy resin and 160g YW-3 organic-inorganic hybrid resin into the reactor and stir for 40min until the system is uniform. Then add 36g precipitated barium sulfate, 43g talcum powder, 10g iron red, 14g phthalocyanine blue, 10g organic bentonite, 5g BYK-A530, and 4g BYK-333 at 400 rpm. Keep at 900 rpm for 3.5h, test the fineness of the coating to be less than 45μm, then reduce the speed, add 120g glass flakes, 90g xylene, and 10g butanol at 400 rpm and disperse for 1.5h. Filter and package to obtain coating A component A-3.
[0047] Example 4
[0048] A mixture of 80 g of acidic silica sol and 150 g of distilled water was added to the reactor. When the temperature of the system reached 60°C, a mixture of 290 g of ethyl orthosilicate and 330 g of methyltriethoxysilane was added dropwise. The addition was completed in 3 hours. During the addition, the temperature of the reaction system was controlled to be between 60°C and 65°C. After the addition was completed, the system temperature was cooled to less than 50°C, and 30 g of xylene was added. The temperature was raised to reflux, 12 g of solvent was evaporated, and the temperature was cooled. When the temperature was less than 60°C, 100 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 20 g of γ-(2,3-epoxypropoxy)propylmethyldimethoxysilane were added, and the temperature of the system was maintained between 60°C and 65°C. After 1.5 hours, the system was cooled to room temperature to obtain YW-4 organic-inorganic hybrid resin. The mass content of silicon in the organic-inorganic hybrid resin is 37.8%, wherein the silanol equivalent is 1450 g / Eq, and the epoxy equivalent is 1300 g / Eq.
[0049] At 500 rpm, add 270g epoxy resin and 90g YW-4 organic-inorganic hybrid resin into the reactor and stir for 35 minutes until the system is uniform. Then add 40g precipitated barium sulfate, 55g talcum powder, 15g iron red, and 10g organic bentonite at 500 rpm. Keep at 1000 rpm for 4 hours, test the fineness of the coating to be less than 40μm, then reduce the speed, add 130g glass flakes, 65g xylene, and 15g butanol at 500 rpm and disperse for 1.5 hours. Filter and package to obtain coating A component A-4.
[0050] Example 5
[0051] At 300 rpm, add 240g epoxy resin and 200g YW-3 organic-inorganic hybrid resin into the reactor and stir for 30min until the system is uniform. Then add 50g precipitated barium sulfate, 10g talcum powder, 10g titanium dioxide, 8g carbon black, 12g phthalocyanine blue, 10g polyamide wax, 8g BYK-A525, and 12g BYK-333 at 300 rpm. Keep at 1000 rpm for 3.5h, test the fineness of the coating to be less than 45μm, then reduce the speed, add 150g glass flakes at 300 rpm and disperse for 2.0h. Filter and package to obtain coating A component A-5.
[0052] Example 6
[0053] At 350 rpm, add 240g epoxy resin and 180g YW-2 organic-inorganic hybrid resin into the reactor and stir for 40min until the system is uniform. Then add 50g precipitated barium sulfate, 10g talcum powder, 5g phthalocyanine blue, 8g fumed silica, and 5g BYK-333 at 350 rpm. Keep at 950 rpm for 4.5h, test the fineness of the coating to be less than 35μm, then reduce the speed, add 150g glass flakes, 10 xylene, and 40g butanol at 350 rpm and disperse for 1h. Filter and package to obtain coating A component A-6.
[0054] Comparative Example 1
[0055] At 300 rpm, 230 g of epoxy resin, 30 g of precipitated barium sulfate, 20 g of talc, 10 g of titanium dioxide, and 0.5 g of polyamide wax were added to the reactor, and maintained at 800 rpm for 4 h. After the fineness of the coating was tested to be less than 45 μm, the speed was reduced, and 80 g of glass flakes were added at 300 rpm for dispersion for 1.5 h. The coating A component A pair-1 was obtained by filtration and packaging.
[0056] Comparative Example 2
[0057] At 500 rpm, 700 g of epoxy resin, 80 g of precipitated barium sulfate, 80 g of talc, 50 g of titanium dioxide, and 50 g of polyamide wax were added to the reactor, and maintained at 1000 rpm for 6 hours. After the fineness of the coating was tested to be less than 50 μm, the speed was reduced, and 200 g of glass flakes, 100 g of xylene, and 100 g of butanol were added at 500 rpm for dispersion for 3 hours. The coating A component A pair-2 was obtained by filtration and packaging.
[0058] Comparative Example 3
[0059] At 400 rpm, 360 g epoxy resin, 36 g precipitated barium sulfate, 43 g talc, 10 g iron red, 14 g phthalocyanine blue, 10 g organic bentonite, 5 g BYK-A530, and 4 g BYK-333 were added to the reactor, and maintained at 900 rpm for 3.5 h. After the fineness of the coating was tested to be less than 45 μm, the speed was reduced, and 120 g glass flakes, 90 g xylene, and 10 g butanol were added at 400 rpm for dispersion for 1.5 h. The coating A component A pair-3 was obtained by filtration and packaging.
[0060] Performance Testing
[0061] The components prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were respectively subjected to paint matching tests with component B phenolic amine, and the prepared coatings were subjected to relevant performance tests. The coating preparation formula is shown in Table 1.
[0062] Table 1: Paint matching table of different A components and different curing agents
[0063]
[0064] The prepared coating is tested for performance. The 250℃500h project test is mainly to observe the blistering, cracking and shedding of the coating. If any of the above phenomena does not occur, it is considered to have passed the test and marked as "√". If any of the above phenomena occurs, it is considered to have failed and marked as "×". The salt spray resistance performance is tested in accordance with GB / T10125. If it passes, it is marked as "√", and if it fails, it is marked as "×". After baking at 250℃ for 240h, the salt spray resistance is not less than 500h. If it passes the experiment, it is marked as "√", and if it fails, it is marked as "×". The data in the table for resistance to cold and hot cycles from 250℃ to 20℃ are the number of times it can withstand. The test results are shown in Table 2.
[0065] Table 2 Test results of coating performance
[0066]
[0067] By comparison, it was found that the coating prepared by combining organic-inorganic hybrid resin and epoxy resin had better high temperature resistance, resistance to cold and hot cycles, and salt spray resistance after baking at 250°C for 240 hours than the coating prepared by pure epoxy resin.
[0068] The preferred implementation modes of the present invention are described in detail above in combination with the embodiments; however, the present invention is not limited to the specific details in the above implementation modes. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical scheme of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0069] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0070] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A high temperature resistant anti-corrosion coating, characterized in that: It includes component A and component B in a mass ratio of (1.1-4):1, wherein: By weight, component A includes: Epoxy resin 15~40 parts 8~30 parts of organic-inorganic hybrid resin Glass flakes 8~20 pieces 3~8 parts of precipitated barium sulfate 2~8 parts of talcum powder 1~5 parts of pigment Additives 0.05~5 parts Solvent 0~20 parts; The preparation method of the organic-inorganic hybrid resin is as follows: 2-30 parts of acidic silica sol are added to 0-20 parts of water, and when the temperature of the system reaches above 60°C, 10-30 parts of a mixture of ethyl orthosilicate and 30-40 parts of methylsiloxane monomers are added dropwise, and the addition is completed in 2-3 hours. During the addition, the temperature of the reaction system is controlled to be between 60-65°C, and after the addition is completed, the system temperature is cooled to less than 50°C, and then 3-15 parts of solvent are added, and the temperature is raised to reflux of the system, and 20-40% of the solvent by weight of the system is evaporated, and then the temperature is cooled, and after the temperature is less than 60°C, 5-15 parts of a silane coupling agent containing an epoxy group are added, and the temperature of the system is maintained between 60-65°C, and the system is cooled to room temperature after reacting for 1-1.5 hours; Component B is phenalkamine.
2. The high temperature resistant anti-corrosion coating according to claim 1, characterized in that: The epoxy resin is a bisphenol A epoxy resin with an epoxy equivalent of 154-450.
3. The high temperature resistant anti-corrosion coating according to claim 1, characterized in that: The diameter of the acidic silica sol particles is 5 to 20 nm; and / or The methylsiloxane monomer is at least one of methyltriethoxysilane and methyltrimethoxysilane; and / or The epoxy group-containing silane coupling agent is at least one of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltriethoxysilane, γ-(2,3-epoxypropyloxy)propylmethyldimethoxysilane and γ-(2,3-epoxypropyloxy)propylmethyldiethoxysilane.
4. The high temperature resistant anti-corrosion coating according to claim 1, characterized in that: The pigment is selected from at least one of titanium dioxide, carbon black, iron oxide red and phthalocyanine blue.
5. The high temperature resistant anti-corrosion coating according to claim 1, characterized in that: The auxiliary agent is selected from at least one of polyamide wax, fumed silica, organic bentonite, BYK-A530, BYK-A525, BYK-A535 and BYK-333.
6. The high temperature resistant anti-corrosion coating according to claim 1, characterized in that: The phenalkamine is selected from at least one of KMH-100, KMH-151, KMH-153, NX-2015, and NX-2018.
7. The method for preparing the high temperature resistant anticorrosion coating according to any one of claims 1 to 6, characterized in that: The preparation method of component A is as follows: epoxy resin and organic-inorganic hybrid resin are mixed evenly, and then precipitated barium sulfate, talcum powder, pigment and additives are added, and after mixing until the fineness is less than 50 μm, glass flakes and solvent are added and dispersed evenly.
